Analisis Rasio Keuangan PT. Bintang Mitra Semestaraya Tahun 2017-2021 - Setiawan, Adi; Martaliah , Nurfitri; Rifadli D. Kadir (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2022)
Bintang Mitra Semestaraya Tbk is a business entity domiciled in the investment and commercial sector. The company started as an investment company investing in real estate companies in developing basic housing projects, mid-range residential projects and companies developing commercial buildings. The importance of analysis of profitability reports to see the company's ability taken from financial statements with the aim of knowing the efficiency and effectiveness of the use of allocation or use of capital in making operational decisions and maximizing profits. The purpose of this study is to see the level of profitability of the Bintang Mitra Semestaraya company from 2017-2021. To examine the data, the researcher uses a financial scale comparison analysis technique in 2021 by comparing previous years (time series technique) or by comparing the achievements of the current period with the previous period so that the differences in each period are obtained using the profitability ratio. With a profitability ratio, the average value shows 6.37%, and the average profit achieved in the last five years is only 1.18% so that the company is declared unable to generate a large enough profit for the company.